SCO in the System of Eurasian Regional Organizations - I. Safranchuk (Международная аналитика)
The paper describes substantial differences between EAUA and Economic Belt of Silk Road, as well as SCO role in the process of political dialogue in Eurasia, its character as a discussion club, the platform of most important political initiatives and real actions able to provide the political unity in SCO.